The rapid rise of generative AI and its implications for academic integrity: Students’ perceptions and use of chatbots for assistance with assessments - Jan Henrik Gruenhagen; Peter M. Sinclair; Julie-Anne Carroll; Philip R.A. Baker; Ann Wilson; Daniel Demant (Computers and Education: Artificial Intelligence)
The rapid adoption of generative AI tools such as ChatGPT by students has the potential to disrupt the higher education sector, with concerns being raised by academics about potential threats to academic integrity. This paper contributes to the pressing discussion about responses to AI tools by examining students' perceptions and the use of generative AI to assist them with assessments. Based on a survey among 337 Australian university students, this study found that more than a third of students have used a chatbot for assistance with an assessment, and do not necessarily perceive this as a breach of academic integrity. The study further investigated to what extent different psychosocial factors such as learning motivations, distress or resilience are associated with students’ use of AI chatbots in order to ascertain environmental conditions or risk factors driving their use. Findings suggest that the higher education sector faces the challenge of not only defining clear policies and guidelines about ethical and academically honest ways to use and integrate generative AI tools into university education and assessments, but also to rethink the design of assessment pieces.